Crossing the borders of time ebook A true story of war, exile, and love reclaimed. - Maitland, Leslie (2012)
On a pier in Marseille in 1942, with desperate refugees pressing to board one of the last ships to escape France before the Nazis choked off its ports, an 18-year-old German Jewish girl was pried from the arms of the Catholic Frenchman she loved and promised to marry.  As the Lipari carried Janine and her family to Casablanca on the first leg of a perilous journey to safety in Cuba, she would read through her tears the farewell letter that Roland had slipped in her pocket: “Whatever the length of our separation, our love will survive it, because it depends on us alone. I give you my vow that whatever the time we must wait, you will be my wife. Never forget, never doubt.”     Five years later – her fierce desire to reunite with Roland first obstructed by war and then, in secret, by her father and brother – Janine would build a new life in New York with a dynamic American husband.  That his obsession with Ayn Rand tormented their marriage was just one of the reasons she never ceased yearning to reclaim her lost love.      Investigative reporter Leslie Maitland grew up enthralled by her mother’s accounts of forbidden romance and harrowing flight from the Nazis. Her book is both a journalist’s vivid depiction of a world at war and a daughter’s pursuit of a haunting question: what had become of the handsome Frenchman whose picture her mother continued to treasure almost fifty years after they parted? It is a tale of memory that reporting made real and a story of undying love that crosses the borders of time.